2014
DOI: 10.1590/1982-021620141112
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de educação em saúde auditiva

Abstract: Objetivo: este estudo pretende apresentar um modelo de educação em saúde auditiva com Teleducação Interativa desenvolvido pelo Departamento de Fonoaudiologia da FOB-USP, enfatizando a importância da criação de materiais educacionais numa proposta de educação profissional e ao paciente na área de Audiologia.Método: foi elaborado um modelo de educação em saúde auditiva baseado na Teleducação Interativa a partir da união de informações acerca dos projetos desenvolvidos e levantamento cronológico da elaboração dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
4
0
6
Order By: Relevance
“…40 The same was observed in the other study, which aim was to develop and analyze the effectiveness of a Hearing Health Training Program (Hearing aids) through interactive teleeducation. 13 Regarding the four domains analyzed ("organized," "easy to use," "stimulating" and "significant"), the scores varied from 22.8, 22.4, 22.5 and 22.2 (►Table 1), as a previous study that developed the FM System Portal and used the MRS with results that varied from 22.52, 22.32, 21.97 and 21.45. 24 Therefore, it is important to reflect on the facilities promoted by telehealth, as well as its assistance in the continuing education of speech therapists, thus it is suggested that the Portal do Zumbido be continually updated due to the need to provide current scientific information to professionals working with this population.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…40 The same was observed in the other study, which aim was to develop and analyze the effectiveness of a Hearing Health Training Program (Hearing aids) through interactive teleeducation. 13 Regarding the four domains analyzed ("organized," "easy to use," "stimulating" and "significant"), the scores varied from 22.8, 22.4, 22.5 and 22.2 (►Table 1), as a previous study that developed the FM System Portal and used the MRS with results that varied from 22.52, 22.32, 21.97 and 21.45. 24 Therefore, it is important to reflect on the facilities promoted by telehealth, as well as its assistance in the continuing education of speech therapists, thus it is suggested that the Portal do Zumbido be continually updated due to the need to provide current scientific information to professionals working with this population.…”
Section: Discussionmentioning
confidence: 96%
“…In this module, important concepts regarding the symptom (classification, cure), scientific articles dealing with the topic, and specific books of audiology were used, as well as other studies that also had as an objective the development of virtual platforms of information. 9,12,13,24 The second module, "audiological diagnosis," contemplates the main procedures performed for the assessment of hearing and to detect the presence or absence of hearing loss. 26 The importance of developing a module on this topic is due to the fact that tinnitus occurs as an isolated idiopathic symptom or related to any type of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devido às extensas dimensões geográficas do Brasil, há uma heterogeneidade na distribuição de fonoaudiólogos, assim, a Telessaúde vai ao encontro das necessidades de descentralização do conhecimento especializado para profissionais da saúde (BLASCA et al, 2014). Portanto, tornam-se válidos todos os investimentos em alternativas que auxiliem na capacitação de profissionais que trabalham na área da saúde, justificando a realização deste estudo, cujo objetivo é a elaboração e avaliação de uma plataforma virtual sobre gerenciamento do zumbido, para fornecer acesso técnico científico para fonoaudiólogos.…”
Section: Introductionunclassified
“…Com a realização dos cálculos foi possível observar a alta satisfação com o Portal do Zumbido, visto que os profissionais participantes o consideraram impressionante. O mesmo foi observado no estudo deBlasca et al (2014), cujo objetivo foi desenvolver e analisar a eficácia de um Programa de Capacitação em Saúde Auditiva -AASI por meio da Teleducação Interativa.Além disto, outros estudos desenvolvidos neste sentido também utilizaram a FPM para obter os dados motivacionais dos materiais elaborados por meio da…”
unclassified